Implementation Strategy for Urban Water Supply Policy - World Bank (Washington, DC, 2013)
This report deals with the water sector in Cambodia, and only mentions sanitation aspects in passing. However, it is recognized that the scale of the sanitation challenge is similarly daunting to or even larger than the water challenge, and that progress in sanitation will be as crucial as expanded access to safe water in making a lasting impact on poverty incidence, in particular vulnerability to waterborne diseases. There are two main constraints to broad-based growth in the sector. First is the absence of a comprehensive strategy to channel financing into the sector and to address weak incentives to raise more own-generated funds from user revenues. Second is the capacity of the providers to absorb public funding and utilize resources efficiently towards expanded access to sustainable services. Both of these constraints will have to be addressed in the context of the country's overall policy of promoting sustainable use of water resources and considering concerns of the poor and marginalized in the pursuit of development. In the short term, the implementation strategy calls for the consolidation of individual investment projects in form of a comprehensive medium-term capital investment program (MTEF), which will serve as a planning tool for investments by the service providers, irrespective of funding source. Over the next years, the broader process of decentralization will have an impact on public and private providers, notably on investment planning decisions and corporate governance of utilities.